SARS-CoV-2 Causes a Different Cytokine Response Compared to Other Cytokine Storm-Causing Respiratory Viruses in Severely Ill Patients - Olbei, Marton; Hautefort, Isabelle; Modos, Dezso; Treveil, Agatha; Poletti, Martina; Gul, Lejla; Shannon-Lowe, Claire D.; Korcsmaros, Tamas (Frontiers in Immunology, 2021)
Hyper-induction of pro-inflammatory cytokines, also known as a cytokine storm or cytokine release syndrome (CRS) is one of the key aspects of the currently ongoing SARS-CoV-2 pandemic. This process occurs when a large number of innate and adaptive immune cells activate, and start producing pro-inflammatory cytokines, establishing an exacerbated feedback loop of inflammation. It is one of the factors contributing to the mortality observed with COVID-19 for a subgroup of patients. CRS is not unique to SARS-CoV-2 infection; it was prevalent in most of the major human coronavirus and influenza A subtype outbreaks of the past two decades (H5N1, SARS-CoV, MERS-CoV, H7N9). With a comprehensive literature search, we collected changing cytokine levels from patients upon infection with the viral pathogens mentioned above. We analysed published patient data to highlight the conserved and unique cytokine responses caused by these viruses. Our curation indicates that the cytokine response induced by SARS-CoV-2 is different compared to other CRS-causing respiratory viruses, as SARS-CoV-2 does not always induce specific cytokines like other coronaviruses or influenza do, such as IL-2, IL-10, IL-4 or IL-5. Comparing the collated cytokine responses caused by the analysed viruses highlights a SARS-CoV-2 specific dysregulation of the type-I IFN response, and its downstream cytokine signatures. The map of responses gathered in this study could help specialists identify interventions that alleviate CRS in different diseases, and evaluate whether they could be used in COVID-19 cases.